2018
DOI: 10.1002/sctm.18-0042
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Fibrotic Effects of Human Amniotic Membrane Mesenchymal Stem Cells and Their Potential in Corneal Repair

Abstract: Acute ocular chemical burns are ophthalmic emergencies requiring immediate diagnosis and treatment as they may lead to permanent impairment of vision. The clinical manifestations of such burns are produced by exacerbated innate immune response via the infiltration of inflammatory cells and activation of stromal fibroblasts. New therapies are emerging that are dedicated to repair mechanisms that improve the ocular surface after damage; for example, transplantation of stem cells (SC) has been successfully report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 59 publications
1
83
0
Order By: Relevance
“…They originate from the extra-embryonic mesoderm of the primitive streak, suggesting high cellular activity and differentiation capacity; they are capable of differentiating into chondrocytes in culture; and they have been identified to have similar phenotypes and characteristics to BMSCs, but with a stronger amplification and differentiation ability (Alviano et al, 2007;Ilancheran et al, 2007;Wei et al, 2009;Liu et al, 2016). They also exhibit non-immunogenicity and immunoregulatory activity, as well as an anti-fibrotic effect (Tsuno et al, 2012;Liu et al, 2016;Navas et al, 2018). Furthermore, they belong to the lineage of the mesoderm, the same germ layer as chondrocytes, and additionally, their resident environment, the amnion, is also a tissue without blood vessels, nerves, or lymphoid tissue, quite similar to the joint cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…They originate from the extra-embryonic mesoderm of the primitive streak, suggesting high cellular activity and differentiation capacity; they are capable of differentiating into chondrocytes in culture; and they have been identified to have similar phenotypes and characteristics to BMSCs, but with a stronger amplification and differentiation ability (Alviano et al, 2007;Ilancheran et al, 2007;Wei et al, 2009;Liu et al, 2016). They also exhibit non-immunogenicity and immunoregulatory activity, as well as an anti-fibrotic effect (Tsuno et al, 2012;Liu et al, 2016;Navas et al, 2018). Furthermore, they belong to the lineage of the mesoderm, the same germ layer as chondrocytes, and additionally, their resident environment, the amnion, is also a tissue without blood vessels, nerves, or lymphoid tissue, quite similar to the joint cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have previously shown that TSG‐6 secreted by human AM mesenchymal stem cells (hAM‐MSCs) is able to inhibit the activation of neutrophils; therefore, an inhibition at an early stage of the innate immune response could modulate an early improvement in CTS symptoms (Magana‐Guerrero, Dominguez‐Lopez, Martinez‐Aboytes, Buentello‐Volante, & Garfias, 2017). Also, conditioned medium from hAM‐MSC was able to downregulate the expression of α‐SMA in an acute ocular chemical burn model inhibiting corneal fibrosis; thus, the biomolecules secreted by AM cells might be able to inhibit perineural fibrosis, ameliorating CTS symptoms after CTRS (Navas et al, 2018). On the other hand, deepithelized AM exerted a selective caspase 3‐dependent apoptosis of the immune cells, while allowing epithelial cells to grow (Garfias et al, 2011); therefore, the effect of AM could be due to stromal matrix–nerve direct contact.…”
Section: Discussionmentioning
confidence: 99%
“…In atopic dermatitis, hMSCs were demonstrated the therapeutic functions in response to Th2 cytokines to mitigate dermatitis through suppressing MCs degranulation . In vitro, MSC was able to diminish human keratocyte differentiation into α‐SMA + limbal myofibroblast, and reduce the release of neutrophil extracellular traps, thus to promote corneal wound healing in an anti‐inflammatory and anti‐fibrotic way …”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…197 In vitro, MSC was able to diminish human keratocyte differentiation into α-SMA + limbal myofibroblast, and reduce the release of neutrophil extracellular traps, thus to promote corneal wound healing in an anti-inflammatory and antifibrotic way. 198 Second, MSC can act on myofibroblasts, the main effector cells in HS formation. It was proved that bone marrow-derived MSCs inhibit myofibroblasts proliferation, migration, ECM synthesis, and scar formation through paracrine signalling.…”
Section: Conclusion and Prospectmentioning
confidence: 99%